Penggunaan Minyak Lavender dalam Menurunkan Kecemasan pada Pasien Hemodialisis - Aat Sriati; Taty Hernawaty; Mutia Sundari; Sarah Kusumah Bakti (Jurnal Keperawatan Silampari, 2022)
This study aims to map the evidence regarding using lavender oil to reduce anxiety in hemodialysis patients. The research method used is Scoping review by systematically searching three databases: PubMed, Google Scholar, and Science Direct. The research results obtained five articles that meet the criteria. The main findings reveal that using lavender oil can reduce anxiety in hemodialysis patients. There are various methods of using lavender oil, which is given by inhalation (dropped in boiled water or dripped onto cotton/gauze/pillow) and gentle massage on the pruritic area. The duration of using lavender oil is between one week and six weeks. In conclusion, using lavender oil can be one of the interventions nurses can carry out to reduce anxiety in hemodialysis patients. Keywords: Anxiety, Lavender Oil, Hemodialysis Patients